ANALYSIS OF THE FOUR ACCOUNTS OF CONTENT CREATORS USING TIKTOK APPLICATION AS TEACHING ENGLISH MEDIA - Eka Listiyowati; Nurjanah Nurjanah; Nina Dwiastuty (Asosiasi dosen IDEBAHASA KEPRI, 2023)
TikTok is an application from China launched in 2016. There are a lot of content creators using TikTok as media to share teaching issues This study aimed at analyzing the presentation of English teaching of four TikTok accounts. This study used qualitative method in the object observation and combined data collection that emphasizes meaning in generalization. Results of this study showed that the four accounts namely Belajar Bahasa Inggris, Aaron’s English, Jago Bahasa, and Kampung Inggris had their own uniqueness in their teaching-English contents. Of 248 videos uploaded by Belajar Bahasa Inggris account, 50% are about word difference. Of 462 videos uploaded by Aaron’s English account, 33% are about word difference. Of 961 videos uploaded by Jago Bahasa account, 36% are discussion about colloquial English. Of 676 videos uploaded by Kampung Inggris account, 35% are discussions about jokes in English. There were similarities and differences in their topic selections such as pronunciation and word difference It was advisable that TikTok users who want to learn English should be able to accurately choose the topics suiting to their interests and needs.